A Case Study on Solar Data Collection and Effects of the Sun's Position in the Sky On Solar Panel Output Characteristics in Northern Cyprus - Jazayeri, Moein; Uysal, Sener; Jazayeri, Kian (IEEE, 2013)
This paper mainly focuses on methods of calculations of sun's position in the sky and analyses of its effects on solar panel output characteristics collected during a case study. Methods for calculations of sun's position in the sky and measurement of solar panel output characteristics are reviewed and then followed by a case study on an experimental data collection system in Northern Cyprus. During the case study, the collected ground measured data are analysed and the results are compared. The solar angle of incidence and the sun's position in the sky are calculated and compared for different time intervals along with panel output characteristics. The short-term data sets belong to three sample days representing sunny, rainy and cloudy conditions in May-2012. The results highlight the effects of sun's position in the sky and the incidence angles of sunlight, during different time intervals and dates, on module output characteristics. The results provide helpful information for researchers and system designers for system yield estimation purposes.
International Conference on Renewable Energy Research and Applications (ICRERA) -- OCT 20-23, 2013 -- Madrid, SPAIN
Keywords: photovoltaics; solar angle of incidence; solar energy; solar data collection; solar radiation; sun's position in the sky